The equiform differential geometry of curves in 4-dimensional galilean space G4 - Aydin, M. Evren; Ergut, Mahmut (Univ Babes-Bolyai, 2013)
In this paper, we establish equiform differential geometry of curves in 4-dimensional Galilean space G(4). We obtain the angle between the equiform Frenet vectors and their derivatives in G(4). Also, we characterize generalized helices with respect to their equiform curvatures.
Keywords: Equiform geometry; generalized helices